Reframing Harmony in Islamic Philosophy: An Epistemological Inquiry into Balance, Ethics, and Moral Agency in Contemporary Muslim Societies - Nurdiyanto Nurdiyanto; Ofik Taufiqurrohman; Habibi Habibi (Harmony Philosophy: International Journal of Islamic Religious Studies and Sharia, 2025)
This study explores how Islamic epistemology can address the fragmentation and ethical challenges in contemporary Muslim societies. By emphasizing the integration of divine revelation and human reason, Islamic epistemology offers a balanced framework for intellectual and spiritual development. The core principles of mīzān (balance), maqāṣid al-sharīʿah (higher objectives of Islamic law), and tawhid (divine unity) form the foundation of Islamic ethical thought, guiding individuals and communities toward social harmony and moral responsibility. The study highlights how these principles can be applied to modern issues such as social justice, environmental sustainability, and the erosion of communal values. Through a comparative analysis, the research contrasts Islamic epistemology with Western ethical frameworks that prioritize individual autonomy, showing how Islamic approaches promote communal accountability and social cohesion. Empirical research, including surveys and interviews, reveals that Muslim communities view Islamic epistemology as a valuable tool for addressing contemporary ethical dilemmas and fostering unity. By revisiting classical Islamic scholars like Al-Farabi, Ibn Sina, and Al-Ghazali, the study provides a theoretical foundation for applying Islamic knowledge to modern day challenges. Additionally, the research examines how the principles of moral agency and personal responsibility in Islamic thought offer solutions to the weakening of ethical conduct in contemporary societies. The study concludes by recommending further research into the practical implementation of Islamic epistemological concepts in governance, education, and social structures to promote ethical and social reform. Integrating Islamic wisdom with modern ethical challenges can offer significant contributions to fostering a more harmonious, just, and ethically responsible global society.